Analisis Teori Produksi Prinsip dan Aplikasinya dalam Ekonomi di Kutai Timur - Noor Azizah; Muhammad Zaini; Andi Santoso; M. Nafarin (STIKes Ibnu Sina Ajibarang, 2025)
This study analyzes the application of production theory in the economy of East Kutai, especially in the mining and oil palm plantation sectors. The main focus is on the basic principles of production theory such as the law of diminishing returns, economies of scale, and isoquant curves, and their relevance in improving production efficiency. The study also considers the perspective of Islamic economics which emphasizes sustainability and justice in production. The results of the study indicate that the application of appropriate production theory can reduce costs and increase output, as well as support sustainable and inclusive economic growth in East Kutai.